The Role of the Kendari City Covid-19 Handling Task Force in Preventing the Spread of the Covid-19 Virus in Kendari City Based on Presidential Regulation Number 82 of 2020 - Aris Nur Qadar Ar.Razak; La Ode Muhammad Iman Abdi Anantomo Uke; Muh. Asrianto Zainal; Aris Darmawan Al Habib; Ahmad Rizal Darwis (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The purpose of this article is to find out the role of the Kendari City Covid-19 Handling Task Force in preventing the spread of Covid-19 in Kendari City. This paper is included in empirical legal research. The results showed: First, the role of the Kendari City Covid-19 Handling Task Force in Preventing the Spread of Covid-19 in Kendari City is divided into 2 steps, namely: 1) prevention steps in the form of: distribution of masks, provision of a place to wash hands and handsanitizer, check body temperature, spraying disinfectants in public places and socializing health protocols in the form of pamphlets and banners. Second, the steps to take in the form of: fines, reprimands and social sanctions. Second, the effectiveness of the Kendari City Covid-19 Handling Task Force in Preventing the Spread of Covid-19 in Kendari City is considered to be at an effective level. This can be seen from the good relationship between the substance of the law (rules regarding the prevention of covid), law enforcement (the Covid 19 Prevention Task Force Team), and Legal culture (legal awerness of the Kendari community).